Analisis Faktor-Faktor Yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan - fitri nuraini; Nanda Diasari; Adhar Putra Setiawan (Majalah Ekonomi, 2023)
This research is quantitative research with the aim of examining the factors (profitability, audit opinion, company size and reputation of the public accounting firm) that influence the accuracy of financial reports of companies listed on the IDX. This sample was taken from food and beverage sub-sector manufacturing companies listed on the IDX. The research sample was selected using a purposive sampling method of 23 food and beverage sub-sector manufacturing companies in 2016 - 2021. The type of research data is secondary data obtained from annual reports of food and beverage sub-sector manufacturing companies in 2016-2021. Data collection is carried out with documentation. In this research, the data source is secondary data collection. The analytical methods used in this research include descriptive analysis, classical assumption testing, multiple linear regression, hypothesis testing. The results of this research show that audit opinion has a significant effect on the timeliness of financial reporting, while profitability, company size and the reputation of the public accounting firm do not have a significant effect on the timeliness of financial reporting. Simultaneous test results of profitability, audit opinion, company size, and reputation of the public accounting firm have a significant effect on the timeliness of financial reporting.